Developing Prepare2Thrive, a community-based intervention targeting treatment engagement among African American individuals living with HIV and serious mental illness. Issue 9 (1st September 2020) - Du Bois, Steve N.; Guy, Arryn A.; Manser, Kelly A.; Thomas, Nicole "Novie"; Noble, Scott; Lewis, Rodney; Toles, Jock; Spivey, Craig; Khan, Humza; Tully, Timothy
ABSTRACT: African American individuals living with HIV and serious mental illness (SMI) may report relatively low treatment engagement, despite treatment engagement being critical to managing both health conditions. Here, we have two aims: to describe the methodology we used to collect focus group data on treatment engagement with a sample of African American individuals living with HIV and SMI, and to describe the results of those focus groups in the context of intervention development. We conducted two focus groups ( N  = 15), integrating a social-ecological model for our theoretical framework, Community-Based Participatory Research for study design and execution, and group concept mapping for data analysis. Three thematic clusters relating to treatment engagement emerged from each group, with overlap across groups: Medication knowledge, Patient-provider relationships, and Barriers to treatment engagement. Items related to the Patient-provider relationship loaded onto all emergent clusters, demonstrating the pervasive impact of this variable. Findings informed the design of Prepare2Thrive, a community-based, culture-specific intervention aiming to increase treatment engagement among African American individuals living with HIV and SMI. Both our design and findings can be used in future collaborations aiming to maximize treatment engagement, and more broadly health, among individuals in this community.